Nutrient fluxes from sediments pose management challenges for the Knysna Estuary, South Africa. Issue 1 (2nd April 2020) - Human, LRD; Weitz, R; Allanson, BR; Adams, JB
Abstract : This study investigated seasonal dynamics of benthic nutrient fluxes using in situ benthic chambers deployed over a 24–hour period at the sediment water interface for four distinct regions of the Knysna Estuary. The sediment in the Upper Estuary, Lagoon and Bay acted as a source of NH4 with a rate of 100–300 µmol m −2 day −1 N, and soluble reactive phosphorus (SRP) with a rate of 15 µmol m −2 day −1 P, whereas that of Ashmead channel exceeded these rates by far. The sediment acted as a sink for NO3 − with fluxes of between −200 and 100 µmol m −2 h −1 . Benthic nutrient fluxes in the estuary were positively related with sediment organic content and silt. Nutrient fluxes in the Ashmead channel were significantly greater than the other regions because of the anoxic sediment, reduced flushing and a legacy of pollutant and organic matter retention. This condition can only be improved by removing wastewater input and dredging. Such drastic interventions are necessary to improve the health of South Africa's top ranked estuary in terms of biodiversity importance.